Scarlet - Bendis, Brian Michael; Maleev, Alexander (New York : Marvel Worldwide, Inc., 2011)
The story of a woman pushed to the edge by all that is wrong with the world and discovers within herself the power to start a modern American revolution.
"Contains material originally published in magazine form as Scarlet #1-5"--Tp verso.
What will the world look like when someone stands up and say, "Enough"? Scarlet is the story of a woman pushed to the edge by all that is wrong with the world...A woman who will not back down...A woman who discovers within herself the power to start a modern American revolution!!
Keywords: Vigilantes -- Comic books, strips, etc; Graphic novels; Portland (Or.) -- Comic books, strips, etc